Surface Integrity Analysis of Wire Electric Discharge Machining of Nitinol Shape Memory Alloy: A Literature Review - Mofoluwaso Kehinde Adeniran; Sunday Ayoola Oke (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
When nitinol is machined, quantitative details regarding the surfaces such as the surface crack density, utmost peak-to-valley heights, recast layer thickness and the mean peak-to-valley height among others offer the most appropriate features to consider in the integrity of the surfaces of machined nitinol. This quantitative information directs the integrity and the projected future performance of the machined nitinol in the components. Consequently, the research question of how to achieve optimal surface integrity of the machined nitinol is important. A literature review is conducted to study the surface integrity analysis of wire electrical discharged machined nitinol. In particular, published papers between 2007 and 2021 have been reviewed. Literature is explored concerning the method of analysis, parameters of research interest and the problems/issues arising from the literature. Diverse methods were employed to evaluate the surface integrity of nitinol after machining. Commonly, both mathematical optimization and microstructural characterizations are used to suggest ideas. Mathematical optimization has been in two broad perspectives, namely, experimental design-based methods such as orthogonal arrays, signal-to-noise ratios, Taguchi's utility and quality loss function, Box-Behnken design and response surface methodology. The non-traditional optimization schemes such as the differential evolution, multi-objective optimization based on ratio analysis and teaching learning-based optimization have been applied. For microstructural characterization, tools to evaluate the surface integrity of nitinol such as field emission scanning electron microscope and energy dispersive X-ray have been deployed. Parameters such as residual stress, geometric deviation, microhardness and profile accuracy are pursued to be optimized. It is known that various literature reviews in previous years have studied the surface integrity problem of nitinol using large-scale approaches. However, in this article, a brief review is prescribed and this work reveals how the surface integrity analysis of nitinol has been tackled in the literature.